ANALISIS KEMAMPUAN LITERASI NUMERASI SISWA SMP PADA ERA MERDEKA BELAJAR - Salsabilah Khoirunnisa; Alpha Galih Adirakasiwi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Numerical literacy skills have an important role in the current era of independent learning, with good numeracy literacy skills students are able to solve problems as well as think critically about the problems they face. The purpose of this study was to analyze students' numeracy literacy abilities in the independent learning era. The subjects to be studied were class VIII students of junior high schools in Karawang Regency consisting of 35 students who had implemented the Independent Curriculum. This study uses a qualitative descriptive research method. The data collection technique used in this study used a description test totaling 5 items on data presentation, while indicators of numeracy literacy skills include: 1) Being able to use various types of numbers and symbols related to basic mathematical operations to solve problems in everyday life; 2) Can analyze information in various forms (graphs, tables, charts, diagrams, etc.); and 3) Interpret the analysis results in order to predict, formulate, and make decisions. The data analysis technique is in the form of the average percentage of each indicator of numeracy literacy ability. Based on the results of the analysis of the data obtained for each indicator, the numeracy literacy skills of junior high school students in the independent learning era were at a low level of 37%.